Exploring Leadership Styles in Nonprofit and For-Profit Acute Care Hospitals - Olsen, Julie A. (My University, 2020)
The cost of healthcare is rising with the US spending $3.6 trillion, which was 17.7% of the US GDP in 2018 (National Health Expenditure Data, 2019). As a result, healthcare has become a major focus of public administrators, politicians, employers, and the general public. Healthcare administrators are searching for new ways to meet the challenges. One strategy is mergers and acquisitions. From 1975 to 2017, the number of for-profit hospitals grew 70.5%, predominately through the acquisition and transition of nonprofit hospitals to for-profit centers, creating large for-profit healthcare systems. Nonprofit hospitals are also acquiring hospitals and creating large nonprofit systems. With more acquisitions and mergers, it is important to understand the impact on leadership, however, there have been few studies in this area. With the trend towards leaders transitioning between business sectors, this study sought to determine if there is a difference in the leadership styles between sectors. Healthcare leaders participated in the Multifactor Leadership Questionnaire designed to determine a leaders’ propensity towards utilizing transformational, transactional, and passive avoidant behaviors. Additional insight was gained through interviews with 20 healthcare leaders with experience in nonprofit and for-profit hospitals. The results revealed no significant difference in transformational behaviors between leaders in the nonprofit and for-profit sectors however for-profit leaders had a stronger tendency towards transactional behaviors in the managing by exception active dimension. The size of the organization appeared to impact the tendency towards transactional behavior. The study considered turnover which was found not to correlate to leadership style. Keywords: leadership; For-profit leadership styles; Nonprofit leadership styles; healthcare leadership; leadership style factors; Transformational leadership;
List of Tables vii -- ACKNOWLEDGEMENTS viii -- Chapter I: INTRODUCTION 1 -- Overview 1 -- Problem Statement 2 -- Conceptual Framework 3 -- Research Goals: Focus and Purpose 4 -- Summary of Methodology 5 -- Significance of the Study 6 -- Limitations of the Study 7 -- Organization of the Study 7 -- Definition of Terms 9 -- Chapter II: REVIEW OF THE LITERATURE 12 -- Healthcare Environment 12 -- Business Models in the Acute Care Setting 15 -- The Function of Leadership in an Organization 18 -- The Concern of Turnover in Healthcare 20 -- Leadership Theory and Leadership Styles 22 -- Size and Other Factors That Determine Leadership Style 33 -- Studies on Leadership Styles 33 -- Chapter III: RESEARCH DESIGN AND METHODOLOGY 38 -- Overview 38 -- Research Design 38 -- Design and Variables 41 -- Initial Data Source 42 -- Participant Selection and Sample Size 47 -- Secondary Data Source 49 -- Limitations of the Research 50 -- Chapter IV: RESULTS 52 -- Summary of Respondent Demographics 52 -- Leadership Survey Results 55 -- Business Model and Leadership Styles 55 -- Leadership Style Subcategories by Business Sector 58 -- The Impact of a Merger on Leadership Tendencies 60 -- Impact of Hospital Mergers: Analysis by Sub-Categories 61 -- Impact of Organizational Size 64 -- Organizational Size Analysis by Subcategories 65 -- Leadership Characteristics by Position 67 -- Leadership Analysis of Subcategories Based on Current Position 68 -- Gender 70 -- Extra Effort, Effectiveness, and Satisfaction 70 -- Turnover Data 71 -- Qualitative Data 73 -- Organizational Culture 75 -- People Management 79 -- Accountability 82 -- Leadership Challenges and Success 85 -- Organizational Size 88 -- Advice to Healthcare Leaders 92 -- Hypotheses Analyzed 95 -- Research Hypothesis 1 95 -- Research Hypothesis 2 97 -- Research Hypotheses 3 100 -- Research Hypothesis 4 101 -- Chapter Summary 102 -- Chapter V: CONCLUSIONS 104 -- Summary 104 -- Discussion of Results 105 -- Interpretation 107 -- Nonprofit Culture and the Leadership Experience 108 -- For-profit Culture and the Leadership Experience 110 -- Community Commitment 112 -- Size 113 -- Relevance to the Future of Healthcare 115 -- Limitations of the Research 119 -- Recommendations for Future Research 119 -- Conclusion 121 -- References 122 -- APPENDIX A: 133.
Keywords: Dissertations, Academic--United States; Hospitals, Proprietary; Hospitals--Administration; Hospitals--Cost of operation; Leadership--Measurement; Leadership; Medical care; Public hospitals; Transformational leadership